Customer Experience as a Mediator Between Fintech Innovation and Customer Decisions in BSI KCP Malang Kepanjen - Andri Teguh Prasetyo; Djunaedi; Angga Rizka Lidiawan (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
The development of the global banking sector, particularly in the face of digitalization challenges, provides an overview of significant changes in bank operations. Based on data on the number of bank branches from 2020 to 2022, there has been a decline in the number of branches in several banks, such as Conventional Commercial Banks - State-Owned Banks. This decline reflects a shift in focus toward digitalization, requiring banks to pay attention to technology in order to enhance operational efficiency. This study aims to examine the impact of fintech innovation on customer decisions, both directly and through customer experience as a mediator. Focusing on Bank Syariah Indonesia (BSI) KCP Malang Kepanjen, this research investigates how fintech innovations, such as mobile banking applications, influence customers' decisions in choosing digital banking services. In addition, this study explores the impact of customer experience on their decisions and how a positive experience can enhance satisfaction and customer loyalty to digital services. The findings suggest that fintech innovations implemented by BSI can improve customer experience, which in turn affects customers' decisions to continue using these services. It is hoped that the results of this study can contribute to the development of more effective digital banking strategies, improve customer satisfaction, and strengthen BSI's position in the digital banking industry in the future.